2011
DOI: 10.1021/ma2000652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restricted Phase Segregation and Resultant Nanostructural Heterogeneity on Glass Transition of Nonuniform Acrylic Random Copolymers

Abstract: The glass transition behavior of emulsion polymerized butyl acrylate (BA)−methyl methacrylate (MMA) copolymers was related to their microstructural features. Broad transition regions composed of two distinct peaks were observed in both DMA and DSC measurements of copolymers with various comonomer compositions indicating dynamic and microstructural heterogeneity. This was further investigated using 2D WISE experiment. Nanophase segregation within the copolymers was inferred from detailed analysis of their local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Kwak and Kim 10 reported the observation of local phase separation into sea-island structures in crude NBRs from the analysis of the spin-lattice relaxation time T 1r of CH 2 . Faghihi et al 8 reported that random copolymers of butyl acrylate and methyl methacrylate showed nanophase segregation according to DMA, DSC and 13 C-NMR spin diffusion experiments. Kipper et al 9 reported that random copolymers of 1,6-bis(p-carboxyphenoxy)hexane and sebacic acid undergo microphase separation because of large differences in the segment-segment interaction parameters.…”
Section: Pulsed 1 H-nmr Analysis Of Crude Nbrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwak and Kim 10 reported the observation of local phase separation into sea-island structures in crude NBRs from the analysis of the spin-lattice relaxation time T 1r of CH 2 . Faghihi et al 8 reported that random copolymers of butyl acrylate and methyl methacrylate showed nanophase segregation according to DMA, DSC and 13 C-NMR spin diffusion experiments. Kipper et al 9 reported that random copolymers of 1,6-bis(p-carboxyphenoxy)hexane and sebacic acid undergo microphase separation because of large differences in the segment-segment interaction parameters.…”
Section: Pulsed 1 H-nmr Analysis Of Crude Nbrsmentioning
confidence: 99%
“…Although almost all random copolymers show homogeneous morphology, it has been reported that some random copolymers show an inhomogeneous phase structure. 8,9 In the case of NBRs, the existence of phaseseparated structures was suggested by the spin-lattice relaxation time (T 1r ) analysis of CH 2 via the 13 C-NMR inversion recovery method. 10 According to these reports, the inhomogeneity was caused by an intramolecular inhomogeneous structure composed of segments with different monomer sequences and by large differences in the segmental interaction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions regarding [35,36]. Compositions of the MMA-rich and BA-rich copolymers of MBC30 were estimated using the Fox equation and T g s of neat PBA and PMMA, −51 and 112°C [28], respectively. The FloryHuggins interaction parameter, χ, of emulsion copolymerized MBC30: the MMA-rich (MBC91) and BA-rich (MBC25) copolymers was also calculated at different temperatures using Mayes' compressible regular solution model [37].…”
Section: Discussionmentioning
confidence: 55%
“…4a), introduced by Fredrickson and Larson [27]. The two-phase UCST copolymer blend composed of butyl acrylate-rich (BA-rich) and methyl methacrylate-rich (MMA-rich) copolymers [28,29]. Filippone and de Luna [30] also assigned the elastic modulus enhancement toward a steady state to either networking among nanoparticle clusters interspersed with the host polymer or non-interacting nanocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…The width of the effective damping region coincides with the glass transition region, which is dominated by the dynamic heterogeneity of chain relaxation 8 , 9 . Based on this mechanism, strategies of tuning dynamic heterogeneity to broaden the frequency range have been developed, such as adding nanofillers 10 12 , blending polymers 13 15 , polymer/organic molecules hybrids 16 , 17 , copolymerization 8 , 18 , gradient polymers 19 , 20 , interpenetrating polymer networks 21 , 22 , and polymers with dangling chains 23 25 . However, all these strategies cannot significantly broaden the effective damping region due to the limitation of inherently narrow glass transition regions for general polymer materials, with a frequency range normally spanning 10 2 Hz 26 .…”
Section: Introductionmentioning
confidence: 79%